The Development of Science Learning Media Etno-Vlog Fermentation Cencaluk in Riau - Minda Azhar; Yohandri Yohandri; Raudhah Awal (Postgraduate, University of Mataram, 2022)
Ethno-Vlog is one of the innovations of learning media to convey material to students. The purpose of this study was to develop a product in the form of learning media and to know the quality of its development seen from its validity and practicality in science learning. This research is development research referring to the ADDIE development model, namely Design, development, implementation, and Evaluation. The media is validated by validators, namely media experts and material experts. The data obtained will be analyzed by descriptive percentage. Furthermore, a practical test was conducted on the validated ethno-vlog media, to educators and students as media users. Based on the questionnaire given, the average value of media validation is 86.6% and material validation is 91.6% which is included in the very good category. Furthermore, the practicality test obtained from the responses of educators and students obtained an average score of 85.6% and 87% with a very satisfied category. It can be concluded that the product resulting from this research in the form of ethnoscience integrated cencaluk fermentation ethnolog media is suitable for use in science learning